(untitled) (Global Journal of Human-Social Science, 2019)
This study empirically investigated the impact of emotional stability on self-efficacy and organizational commitment of Saving and Credit Co-operative SACCOS employees of Kathmandu The total sample consisted of 400 employees Males 152 Females 248 The samples obtained from 112 SACCOS This research focused on emotional stability trait of International Personality Item Pool IPIP originally developed by Goldberg 1992 This analytical research examined the Co-operative employees emotional instability by using the Mini IPIP five-factor model of Donnellan Oswald Baird Lucas 2006 The result of this study reported that the Mean score 8 76 of females excelled the Mean score 0 07 of males The previous research found that female employees Mean score of emotional stability was significantly lesser than the male counterpart Basnet Regmi 2018 36 and the other standardize scales used to report the results